2016
DOI: 10.5114/jcb.2016.59686
|View full text |Cite
|
Sign up to set email alerts
|

Prostate-specific antigen nadir after high-dose-rate brachytherapy predicts long-term survival outcomes in high-risk prostate cancer

Abstract: PurposeTo evaluate the prognostic value of prostate-specific antigen nadir (nPSA) after high-dose-rate (HDR) brachytherapy in clinically non-metastatic high-risk prostate cancer patients.Material and methodsData from 216 patients with high-risk or locally advanced prostate cancer who underwent HDR brachytherapy and external beam radiation therapy with long-term androgen deprivation therapy (ADT) between 2003 and 2008 were analyzed. The median prostate-specific antigen (PSA) level at diagnosis was 24 ng/ml (ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 33 publications
(39 reference statements)
2
11
0
Order By: Relevance
“…Previous studies suggested that the PSA nadir after radiotherapy is well correlated with prognostic values . In the present study, the proportion of patients who reached a PSA level of less than 0.02 ng/mL after radiotherapy was significantly higher in patients with MDRT than those without MDRT.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…Previous studies suggested that the PSA nadir after radiotherapy is well correlated with prognostic values . In the present study, the proportion of patients who reached a PSA level of less than 0.02 ng/mL after radiotherapy was significantly higher in patients with MDRT than those without MDRT.…”
Section: Discussionsupporting
confidence: 50%
“…Previous studies suggested that the PSA nadir after radiotherapy is well correlated with prognostic values. 15,16 In the present study, the proportion of patients who reached a PSA level of less than 0.02 ng/mL after radiotherapy was significantly higher in patients with MDRT than those without MDRT. These results may reflect that ablative radiotherapy to all metastatic sites, in addition to definitive prostate radiotherapy, could achieve lower PSA nadir values and consequently improve CRPC-free survival in newly diagnosed oligometastatic prostate cancer patients.…”
Section: Radiotherapy For Metastasissupporting
confidence: 45%
“…Our treatment protocol for HDR‐BT, EBRT, and hormone therapy in high‐risk prostate cancer was previously reported and is shown in Figure . All patients initially underwent at least 6 months of neoadjuvant ADT, and adjuvant ADT was continued for 36 months after completion of radiotherapy.…”
Section: Methodsmentioning
confidence: 99%
“…Although no further long-term survival data were reported for these two radiation modalities in localized, high-risk patients, LDR-BT is generally administered as a monotherapy in early diagnosed cases, while HDR-BT is usually applied along with EBRT in cases of prostate cancer in unspecified stages [ 28 ]. In addition, some clinical trials found that a PSA nadir of less than 0.02 ng/mL within 12 months of radiotherapy is associated with significantly improved biochemical tumor control and cause-specific survival in cases of locally advanced and non-metastatic high-risk prostate cancer co-administered HDR-BT, EBRT, and long-term ADT [ 29 ]. Thorsten et al reported a discrepant conclusion regarding the predictive value of PSA for the biochemical control rate in 79 cases with high-risk PCa administered HDR-BT following EBRT, with an average follow-up of 21 months; the authors described PSA as a negative predictive biomarker for local recurrence during follow-up, indicating that prolonged follow-up is required for reassessing long-term outcomes [ 30 ].…”
Section: Discussionmentioning
confidence: 99%